Impact of Integrated Yoga Module on Leadership Competencies of Managers - Taware, Datta S.; Kumari, Sony; Akhilesh, K. B.; Nagendra, H. R. (Prabandhan: Indian Journal of Management, 2017)
Leadership remains one of the most researched topics, but scientific mechanisms behind the phenomenon are not yet known completely. Leadership competency is considered as a trait of a leader than a process in the organizational context. The purpose of this research was to explore the impact of integrated yoga module on leadership competencies as given in Indian transformational leadership (ITL) and propose a model for the leadership phenomenon. We conducted a randomized control trial study on a total of 126 managers with 90 days of intervention (integrated yoga module (yoga group) (n = 63) and physical exercise (PhyEx group) (n = 63) participants). Experiments revealed that leadership competencies were affected by both integrated yoga module and physical exercise significantly (p < 0.001). RM ANOVA results showed that yoga group showed high effect of size than physical exercise and had a consistent significant effect over repeated measures. The integrated yoga module was found to have a consistent positive impact on most of the leadership competencies with emotional and cognitive domains requiring willpower and self control, while physical exercise had a positive impact only on emotional domains of leadership competencies.